Evolution and long‐term outcomes of combined immunodeficiency due to CARMIL2 deficiency. Issue 3 (30th July 2021) - Kolukisa, Burcu; Baser, Dilek; Akcam, Bengu; Danielson, Jeffrey; Bilgic Eltan, Sevgi; Haliloglu, Yesim; Sefer, Asena Pinar; Babayeva, Royale; Akgun, Gamze; Charbonnier, Louis‐Marie; Schmitz‐Abe, Klaus; Kendir Demirkol, Yasemin; et al.
Abstract: Background: Biallelic loss‐of‐function mutations in CARMIL2 cause combined immunodeficiency associated with dermatitis, inflammatory bowel disease (IBD), and EBV‐related smooth muscle tumors. Clinical and immunological characterizations of the disease with long‐term follow‐up and treatment options have not been previously reported in large cohorts. We sought to determine the clinical and immunological features of CARMIL2 deficiency and long‐term efficacy of treatment in controlling different disease manifestations. Methods: The presenting phenotypes, long‐term outcomes, and treatment responses were evaluated prospectively in 15 CARMIL2‐deficient patients, including 13 novel cases. Lymphocyte subpopulations, protein expression, regulatory T (Treg), and circulating T follicular helper (cTFH ) cells were analyzed. Three‐dimensional (3D) migration assay was performed to determine T‐cell shape. Results: Mean age at disease onset was 38 ± 23 months. Main clinical features were skin manifestations ( n  = 14, 93%), failure to thrive ( n  = 10, 67%), recurrent infections ( n  = 10, 67%), allergic symptoms ( n  = 8, 53%), chronic diarrhea ( n  = 4, 27%), and EBV‐related leiomyoma ( n  = 2, 13%). Skin manifestations ranged from atopic and seborrheic dermatitis to psoriasiform rash. Patients had reduced proportions of memory CD4 + T cells, Treg, and cTFH cells. Memory B and NK cells were also decreased. CARMIL2‐deficient T cells exhibited reduced T‐cell proliferation and cytokine production following CD28 co‐stimulation and normal morphology when migrating in a high‐density 3D collagen gel matrix. IBD was the most severe clinical manifestation, leading to growth retardation, requiring multiple interventional treatments. All patients were alive with a median follow‐up of 10.8 years (range: 3–17 years). Conclusion: This cohort provides clinical and immunological features and long‐term follow‐up of different manifestations of CARMIL2 deficiency. Abstract : CARMIL2 deficiency results in variable phenotypes encompassing skin disease, combined immune deficiency, early‐onset inflammatory bowel disease, and allergic manifestations. Patients have impaired differentiation of mainly CD4 + T cells, resulting in elevated naïve CD4 + T cells. Gastrointestinal involvement and EBV‐related smooth muscle tumors are major determinants of poor prognosis. Abbreviations: CARMA, CARD‐Containing MAGUK Protein; CARMIL, capping protein regulator and myosin 1 linker 2; CBR, C‐terminal domain including a capping protein binding region; CP, capping protein; HD, homodimerization domain; EBV, Epstein‐Barr virus; LRR, leucine‐rich repeat; NF‐κB, nuclear factor kappa B; PH, pleckstrin homolog; PKCθ, protein kinase C theta; PRR, proline‐rich region; SMT, smooth muscle tumor